2021
DOI: 10.3389/fphar.2020.609811
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Psychostimulants – Are High- and Low-Affinity Organic Cation Transporters Drug Traffickers?

Abstract: Psychostimulants are used therapeutically and for illegal recreational purposes. Many of these are inhibitors of the presynaptic noradrenaline, dopamine, and serotonin transporters (NET, DAT, and SERT). According to their physicochemical properties, some might also be substrates of polyspecific organic cation transporters (OCTs) that mediate uptake in liver and kidneys for metabolism and excretion. OCT1 is genetically highly polymorphic, with strong effects on transporter activity and expression. To study pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 72 publications
(90 reference statements)
1
21
0
Order By: Relevance
“…We also observed that substitutions at the primary nitrogen of the phenylethylamine and tryptamine backbone decreased MAT transport ( Figure 4 and Figure S4 ), this is in line with the historic findings using indirect methods and primary cells [ 26 ]. This also explains the low SERT uptake ratios of the recently shown hallucinogens dimethyl- and diethyltryptamine [ 43 ]. Interestingly and in contrast to the results in MATs, these substitutions at the primary amine improved transport via OCT1 in several cases.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We also observed that substitutions at the primary nitrogen of the phenylethylamine and tryptamine backbone decreased MAT transport ( Figure 4 and Figure S4 ), this is in line with the historic findings using indirect methods and primary cells [ 26 ]. This also explains the low SERT uptake ratios of the recently shown hallucinogens dimethyl- and diethyltryptamine [ 43 ]. Interestingly and in contrast to the results in MATs, these substitutions at the primary amine improved transport via OCT1 in several cases.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we investigated the uptake of different psychostimulants, showing that there is overlap between MATs and OCTs in the uptake of substances which in their chemical structure differ from the typical neurotransmitters. Particularly cathine was transported by both the MATs (DAT and NET), but also by OCT2 [ 43 ]. As opposed to OCT2, OCT1 transported only one of the tested psychostimulants to a significant degree, namely mescaline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some stimulants are major substrates of organic cation transporters (OCTs) that mediate liver and kidney uptake for metabolism and excretion. Methamphetamine, amphetamine, (–)‐ephedrine, and particularly cathine, are important substrates of renal OCT2, with cathinone, MDMA, and MDEA of lesser importance 93,94 . Involvement of OCT2 in the renal tubular secretion and excretion of some stimulants may result in individual differences in toxicity and potential for drug‐drug interaction at this transporter 93,94 …”
Section: Presynaptic/prejunctional Receptorsmentioning
confidence: 99%
“…MDMA may act both to increase heat production and reduce heat loss to increase temperature by up around 2°C, and this can lead to severe hyperpyrexia, presumably by a cascade of prohyperthermic events 129 . Patients also present with symptoms ressembling heat stroke, rhabdomyolysis, myoglobinuria, renal failure, liver damage, and disseminated intravascular coagulopathy, and these symptoms may also occur with amphetamine, metamphetamine, and MDEA 70,30–132 . Cutaneous vasoconstriction to reduce heat loss could explain a major component of the temperature actions of MDMA and derivatives, and this may be mediated largely through peripheral actions at α 1 ‐ and α 2 ‐adrenoceptors rather than central serotonergic actions 133–136 .…”
Section: Hyperthermiamentioning
confidence: 99%